Advances in graphene-based flexible and wearable strain sensors - Chen, Hui; Zhuo, Fengling; Zhou, Jian; Liu, Ying; Zhang, Jinbo; Dong, Shurong; Liu, Xuqing; Elmarakbi, Ahmed; Duan, Huigao; Fu, Yongqing (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
•The strain sensing mechanisms and performance of graphene-based sensors.•The design and fabrication strategies of four graphene-based strain sensors.•The applications of graphene-based flexible strain sensors in numerous fields.•Existing challenges and future opportunities for graphene-based sensors. Flexible and wearable electronics have recently gained considerable research interest due to their potential applications in personal healthcare, electronic skins, and human–machine interfaces. In particular, strain sensors that can efficiently transmit external stimuli into electrical signals are essential for wearable electronics. Two-dimensional carbon-based materials such as graphene are potentially versatile platforms for the above applications, mainly attributed to their combined properties of excellent flexibility, thermal and electrical conductivity, and mechanical strength. Although there are numerous reports devoted to the design, fabrication and application of graphene-based strain sensors, a comprehensive overview dedicated on attributes of graphene-based strain sensors that can be systematically correlated with their mechanisms, fabrication strategies and applications is urgently required in the field. Specially this review is aimed to explore the following topics, i.e., (i) the strain sensing mechanisms and key performance parameters of graphene-based sensors; (ii) the recent progress of major graphene-based sensors including those of film-based, fiber-based, foam-based and hydrogel-based; (iii) applications of graphene-based sensors for human motion sensing, health indicators, electronic skins and human machine interfaces; and finally (iv) challenges and future directions for the design of graphene-based sensors.